PERANCANGAN APLIKASI ENSIKLOPEDI DIGITAL TARI DAERAH BANTEN BERBASIS ANDROID PADA MATA PELAJARAN SENI BUDAYA SISWA KELAS VII - Cahyo Sunarto; Alis Triena Permanasari; Dwi Junianti Lestari (Pendidikan Seni Drama Tari dan Musik, Universitas Sultan Ageng Tirtayasa, 2022)
Abstract : The development of technology moving rapidly which results in significant changes in human life, one of which is the smartphone. Smartphone of the tools that can facilitate the process of disseminating information, communication, and other activities. It can be seen from the many applications that can help the needs and interests of the community, such as online shopping, communication with colleagues, directions, playing games, online payments, and online learning. From the existing phenomena and problems, the researchers carried out further research related to the design of Android-based digital encyclopedia application of Banten regional dance on cultural arts subjects, introduction to local dance materials for SMP class VII. The purpose of this study is to determine the process of designing and manufacture testing the feasibility of android-based learning media. The research method used is research and development (R&D) with the Linear Sequential Model (LSM), it consists of five stages development model 1) requirement namely needs analiysis; 2) design system namely design system; 3) coding & testing namely writing program code/implementation; 4) integration & testing namely application/test program; and 5) operation & maintenance namely maintenance. Based on several assessments of media experts, materials, and users related to learning media with a media expert percentage level of 85.85% the